Mobile-Assisted Flipped Learning Integrated with Metacognitive Skills in the Teaching of Speaking and Listening Skills - Haerazi Haerazi (Journal of English Education and Teaching, 2023)
The integration of mobile technology within the framework of flipped learning provides a viable and efficient means of fostering learners' speaking and listening skills. Through the flipped classroom, learners are better prepared for in-class interactions, as they have already acquired foundational knowledge and exposure to authentic language use. Therefore, this study aims to find out the efficacy of mobile-assisted flipped learning integrated with metacognitive skills in the teaching of speaking and listening skills in Mandalika University of Education. This study is designed in experimental design which is non-equivalent control group design. In this design, participants are not randomly assigned to the intervention or control group, resulting in inherent differences between the groups that may influence the outcomes. The instruments employed the speaking, listening, and metacognitive tests. The collected data are analyzed in descriptive and inferential statistical analysis. Based on the data analysis, the conclusion of this study showed that the integration of mobile-assisted flipped learning had a positive impact on learners' speaking and listening proficiency. Learners actively engaged in preparing their learning activities, both during out-of-class and in-class sessions. The incorporation of mobile technology and the flipped learning approach empowered learners to take ownership of their learning, enabling them to access instructional materials outside the traditional classroom setting and actively participate in in-class interactions. These findings highlight the potential of mobile-assisted flipped learning as an effective pedagogical approach in enhancing learners' speaking and listening skills, while also promoting learner autonomy and engagement in the learning process.